Problem Based Learning Model for Understanding Towards Learning Results of School Students Basketball First Medium Nurul Hasanah - Muhammad Noer Fadlan; Arrini Shabrina Anshor (Berpusi Publishing, 2022)
This study aims to see learning outcomes using a problem based learning learning model, from the results of the research carried out it can be seen and concluded that, Based on the results above, it shows that the learning outcomes of the A1B1 group basketball material have an average pretest of 46.58 and experienced an increase at the posttest of 62.25, group A2B1 the average prestest was 46.84 and an increase at the posttest was 77.84, group A1B2 had an average pretest of 31.10 and increased at the posttest was 49. .92, the A2B2 group had an average pretest of 35.11 and an increase at the time of the posttest was 44.16. Based on the statistical analysis of the normality test carried out using the Shapiro-Wilk test in Table 14 above, it can be seen that all pre-test and post-test data for learning outcomes of basketball, physical education, health sports, come from the results of the normality test. The test data, the significance value of p> 0.05, which means the data is normally distributed. This type of research is an experiment that uses a 2 x 2 factorial design. Based on the results of the study and the results of data analysis, the following conclusions are drawn, there are significant differences in the effectiveness of the problem learning model.